Matlab modeled for real time processing of partial discharge detection using fpga technology with giga hertz data acquisition - Emilliano; Chakrabarty C.K.; Basri A.; Ramasamy A.K.; Devkumar S.; Hock G.C.; Badjian M.H. (2023)
This paper is purely a model to determine the method to advance Partial Discharge (PD) detection. The research shall involve matlab and Verilog High Development Language (VHDL) programming to evaluate the use of Field Programming Gate Array (FPGA) for the detection and counting of partial discharge signals. 2009 WASET.ORG.